Multicystic encephalomalacia in children, the role of infections - V. V. Vlasyuk; Ju. P. Vasileva; A. A. Vilnits; V. E. Karev (Журнал инфектологии)
We describe the cases of ME at different stages of development in 8 children died at the age of 19 days to 2 years 11 months and one surviving child after herpetic encephalitis. We present morphological and neurosonographic changes the brain from the stage of necrosis up to the stage of formation of cysts. The dynamics of structural changes of the cysts. We describe a rare case of giant cyst formation of the cerebral hemispheres in a child born with a mass of 500 g. In the majority of observations for ME postinfectious vasculitis characterized by the brain. Considered signs of differences posthypoxic (ischemic) and postinflammatory foci of necrosis of the brain.